2009
DOI: 10.1177/0269881109348172
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and obsessive-compulsive symptoms and quality of life in children with attention-deficit hyperactivity disorder (ADHD) during three-month methylphenidate treatment

Abstract: The current study was designed to investigate the changes that occur in depression, anxiety, obsessive-compulsive symptoms and health-related quality of life during methylphenidate (MPH) treatment in children with attention-deficit hyperactivity disorder (ADHD). Forty-five treatment naive children with ADHD, aged 8-14, were assessed based on self, parent and teacher reports at the baseline and at the end of the first and third month of MPH treatment regarding changes in inattention, hyperactivity, impulsivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…Improvement in CDI scores was not related to the restoration of the low morning serotonin levels observed in the ADHD group. These clinical data are consistent with those reported by other authors (Tomas Vila et al, 2010;Gurkan et al, 2010). In a 10-year prospective follow-up study among young adults with ADHD, Biederman et al, found evidence that stimulant treatment decreases the risk for subsequent comorbid psychiatric disorders (i.e., depressive and anxiety disorders and disruptive behaviour) and academic failure (Biederman et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Improvement in CDI scores was not related to the restoration of the low morning serotonin levels observed in the ADHD group. These clinical data are consistent with those reported by other authors (Tomas Vila et al, 2010;Gurkan et al, 2010). In a 10-year prospective follow-up study among young adults with ADHD, Biederman et al, found evidence that stimulant treatment decreases the risk for subsequent comorbid psychiatric disorders (i.e., depressive and anxiety disorders and disruptive behaviour) and academic failure (Biederman et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Children's ratings of QoL measurements showed no significant changes in physical health and psychosocial scores, while total scores significantly improved after treatment. The researchers concluded that, over a 3-month MPH treatment, depression, trait anxiety and checking compulsion symptoms decreased and that QoL improved, along with the symptoms of inattention, hyperactivity and impulsivity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…To rate their child's behaviour, the parents respond to each item on a four-point Likert scale: 0, never; 1, rarely; 2, often; 3, always. Diagnostic and Statistical Manual of Mental Disorders —fourth edition (DSM-IV) symptom subscale scores of the CPRS-R were used to determine the severity of the ADHD symptoms 11. The following subscale scores were evaluated: cognitive problems/inattention (CG/I); hyperactivity; Attention Deficit Hyperactivity Disorder Index (ADHD-I); Conners' Global Index—Discomfort-Impulsivity (CGI-DI); DSM-IV symptom subscales—inattention (DSMIV SS-I); DSM-IV symptom subscales—hyperactivity–impulsivity (DSM-IV SS-HI); DSM-IV symptom subscales—total (DSM-IV SS-T).…”
Section: Methodsmentioning
confidence: 99%